VD_FINDINFO Jug / 2023 / 509 vom 17. September 2021 - VD Tribunal cantonal (2021)
DROIT PÉNAL DES MINEURS, ADMISSION PARTIELLE, COMPLICITÉ, BRIGANDAGE | 140 ch. 1 CP, 25 CP, 2 al. 1 DPMin, 23 DPMin, 35 DPMin, 44 PPMin